Karakteristik pasien dan rasionalitas penggunaan obat demam berdarah dengue pada pasien anak rawat inap - Lubis, Salmah Handayani Lubis; Dasopang, Eva Sartika; Siahaan , Desy Natalia; Hasanah, Fenny; Ndruru, Mei Kasih Murni; Aisyah , Teti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Dengue hemorrhagic fever (DHF) is an infectious disease that can affect children. The main principles of DHF treatment are supportive therapy that can reduce mortality to less than 1%, and maintenance of circulating fluid volume. This study aims to determine the distribution of the proportion of DHF patients in children based on age, gender, clinical symptoms and the rationality of the use of DHF drugs in pediatric patients treated at Dr. Pirngadi Medan Hospital. This study was a descriptive nonanalytic study with a case study design. The population data in this study were all medical records of pediatric patients diagnosed with DHF who were treated in the period of 2022 at RSUD Dr. Pirngadi Medan. This study concluded that most pediatric DHF patients were female (47.6%), age 0-35 years (42.7%), clinical symptoms of fever (82%), fever duration of 4 days (82.9%). The most common complaints of pediatric DHF disease were fever (100%), vomiting (81%), nausea (75%). In evaluating the rationality of drug use in the correct dose of analgesic and antipyretic paracetamol administration was obtained 100% (correct dose) and the administration of lactated ringer fluid 85.36% (not correct dose).